2015
DOI: 10.1039/c4dt03291h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evidence of metal-induced structural distortions in a series of bipyrimidine-based ligands

Abstract: Herein, we report theoretical evidence of the geometric changes occurring upon complexation, for a series of octupolar bipyrimidine-based ligands incorporating the NPh2 terminal donor group. It is shown that ligands 1 and 2 (4,4',6,6'-tetrakis(N,N-diphenylaminostyryl)-[2,2']bipyrimidine and 4,4',6,6'-tetrakis((N,N-diphenyl)-9,9'-dioctyl-9H-fluorene-2-amine)-2,2'-bipyrimidine) exhibit a non-planar geometry with a torsion angle between both pyrimidine moieties of ∼25° and 50° respectively. 1a (complex of 1) beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…All MD simulations were performed with the AMBER12 program [ 30 ]. A previous work [ 41 ] by Latouche et al demonstrated that the Gaussian program is able to perform a QM/MM simulation with good accuracy, and thus the sander module with an interface to the Gaussian09 program [ 42 ] was used to carry out the QM/MM MD simulation.…”
Section: Computational Approachesmentioning
confidence: 99%
“…All MD simulations were performed with the AMBER12 program [ 30 ]. A previous work [ 41 ] by Latouche et al demonstrated that the Gaussian program is able to perform a QM/MM simulation with good accuracy, and thus the sander module with an interface to the Gaussian09 program [ 42 ] was used to carry out the QM/MM MD simulation.…”
Section: Computational Approachesmentioning
confidence: 99%
“…However, the latter transition may become partially allowed upon relaxation to conformations with a lower symmetry. 23,24 Therefore, the interarm interaction energy can be estimated to have a value of ca. 0.31 eV for RuTX.…”
mentioning
confidence: 99%
“…In this precise case, one should stress that for pure C 3 symmetry, the S 0 –S 1 transition is one-photon-allowed whereas the S 0 –S 2 one is theoretically one-photon-forbidden. However, the latter transition may become partially allowed upon relaxation to conformations with a lower symmetry. , Therefore, the interarm interaction energy can be estimated to have a value of ca. 0.31 eV for RuTX .…”
mentioning
confidence: 99%
“…1 presents a large molecular structure with a great number of atoms (278). Calculations of both the ground and excited states on molecular compounds of such large size have rarely been conducted 48 and especially on polymetallic systems. 49 The geometries of the singlet ground state (S 0 ) and of the lowest excited triplet state (T 1 ) of 1 have thus been optimized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%